Butterfly wing color: A photonic crystal demonstration. (January 2016) - Proietti Zaccaria, Remo
Abstract: We have theoretically modeled the optical behavior of a natural occurring photonic crystal, as defined by the geometrical characteristics of the Teinopalpus Imperialis butterfly. In particular, following a genetic algorithm approach, we demonstrate how its wings follow a triclinic crystal geometry with a tetrahedron unit base. By performing both photonic band analysis and transmission/reflection simulations, we are able to explain the characteristic colors emerging by the butterfly wings, thus confirming their crystal form. Abstract : Highlights: We model the optical response of the wings of the Teinopalpus Imperialis butterfly. The best matching solution is found by employing a genetic algorithm. The characterization is performed through band structure calculation and reflection analysis.